Predicting future corn suitability zones under climate change scenarios in the United States of America - Birhan Getachew Tikuye; Ram Lakhan Ray (Journal of Agriculture and Food Research)
Global climate change influences agricultural production, water resources, and socioeconomic development, with profound implications for staple crops like corn. Corn is a major crop grown worldwide and is highly vulnerable to climate variability, making it essential to evaluate its future viability amid changing climatic conditions. This study employs the MaxEnt (Maximum Entropy) model to predict spatial changes in corn suitability across the United States under baseline and future climate change scenarios. Corn suitability was assessed using datasets from the USA Department of Agriculture National Agricultural Statistics Service (USDA-NASS) Crop Data Layer (CDL) for 2023 and bioclimatic variables from WorldClim version 2, soil-texture, soil-pH, soil organic carbon, elevation, and slope. Future projections were based on the Coupled Model Intercomparison Project Phase 6 (CMIP6) under two Shared Socioeconomic Pathways (SSP2-4.5 and SSP3-7.0) for the 2050s and 2090s, utilizing an ensemble mean of 13 General Circulation Models (GCMs). Model performance was evaluated using the area under the curve (AUC) of the receiver operating characteristic (ROC) and the coefficient of determination (R2), yielding values of 0.90 and 0.7, respectively. The results indicate that under a moderate-emission scenario (SSP2-4.5), corn suitability may improve in some regions by the 2050s while under a high-emission scenario (SSP3-7.0), rising temperatures and changed precipitation patterns are projected to cause substantial declines in corn production suitability, cultivation, and yield by 4 % by the end of 21st century. The most influential bioclimatic factors affecting corn suitability were precipitation of the warmest quarter, mean temperature of the driest quarter, slope, soil pH, elevation, and soil organic carbon, which explained about 98.5 % of corn suitability variations. As climate change introduces uncertainty into global agriculture, proactive adaptation strategies such as improved irrigation systems, sustainable soil management, and the development of heat-resistant corn varieties will be critical in maintaining yield stability.